Impact of asymptomatic Plasmodium falciparum infection on the risk of subsequent symptomatic malaria in a longitudinal cohort in Kenya - Sumner, Kelsey M; Mangeni, Judith N; Obala, Andrew A; Freedman, Elizabeth; Abel, Lucy; Meshnick, Steven R; Edwards, Jessie K; Pence, Brian W; Prudhomme-O'Meara, Wendy; Taylor, Steve M (eLife, 2021)
Background: Asymptomatic Plasmodium falciparum infections are common in sub-Saharan Africa, but their effect on subsequent symptomaticity is incompletely understood. Methods: In a 29-month cohort of 268 people in Western Kenya, we investigated the association between asymptomatic P. falciparum and subsequent symptomatic malaria with frailty Cox models. Results: Compared to being uninfected, asymptomatic infections were associated with an increased 1 month likelihood of symptomatic malaria (adjusted hazard ratio [aHR]: 2.61, 95% CI: 2.05 to 3.33), and this association was modified by sex, with females (aHR: 3.71, 95% CI: 2.62 to 5.24) at higher risk for symptomaticity than males (aHR: 1.76, 95% CI: 1.24 to 2.50). This increased symptomatic malaria risk was observed for asymptomatic infections of all densities and in people of all ages. Long-term risk was attenuated but still present in children under age 5 (29-month aHR: 1.38, 95% CI: 1.05 to 1.81). Conclusions: In this high-transmission setting, asymptomatic P. falciparum can be quickly followed by symptoms and may be targeted to reduce the incidence of symptomatic illness. Funding: This work was supported by the National Institute of Allergy and Infectious Diseases (R21AI126024 to WPO, R01AI146849 to WPO and SMT).
Keywords: malaria; asymptomatic infection; parasite density